Problem Based Learning in Engineering at the Institute of Engineering: Prospects cum Challenges - Joshi, Rajendra Kumar; Joshi, Milly (Journal of the Institute of Engineering, 2011)
Despite having undergone significant transformations over the last few decades, educational institutes of Nepal are prone to using traditional teaching methods to most extent. This is particularly true of Tribhuvan University. Nevertheless there are all the same few renowned institutes of Tribhuvan University which are not merely open to educational innovations but have strong predisposition to respond positively to the augmenting demand of time vis-à-vis adoption of new educational approaches cum strategies. Institute of Engineering (IOE) is one among them. Albeit Problem Based Learning (PBL) Approach is apparently a new approach in Nepal’s engineering educational scenario, IOE has brought similar approach to bear upon its educational practices in some courses. However, IOE has yet to design fully fledged student-centric problem based curricula over time, considering the efficacy and efficiency of Project based approach in enhancing professional skills, technical expertise and profound understanding of students. This paper aims at delineating on the prospects cum challenges regarding the implementation of PBL approach in engineering programs at the IOE. However, the foremost section of the paper will briefly scrutinize the overall structure and situation of education in Nepal. The second section of the paper will comprehensively outline the educational system and courses offered at the IOE from the scratch. The most important of all, third section will focus upon the prospects and relevancy of introducing PBL component in engineering courses at the IOE. This section will simultaneously deal with potential impediments or constraints to be encountered during the process of implementing PBL approach. The final section of the paper will attempt to elicit a cogent conclusion with viable solutions and tentative plan to implement PBL approach effectively at the IOE against the backdrop of varied constraints. Key words: Faculties; Prospects; Impediments; Affiliated; Constituent DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5125 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 291-300 Uploaded Date: 20 July, 2011